Factors influencing Chinese Non-English majors' attitudes toward blended learning: The role of perceived relevance, online self-efficacy, and teachers' digital literacy - Li, Xin; Sulaiman, Nur Ainil; Aziz, Azlina Abdul (Edelweiss Applied Science and Technology, 2025)
Chinese non-English majors frequently disengage from mandatory college English courses—a persistent challenge despite the widespread adoption of blended learning. This study investigates how students’ attitudes toward these technology-enhanced environments are shaped by (1) perceived course relevance, (2) confidence in online learning (self-efficacy), and (3) perceptions of instructors’ digital literacy. Surveying 300 students across six universities in Zhejiang Province, we analyzed responses using structural equation modeling (SEM). Results indicate that perceived relevance exerts the strongest influence on attitudes (β = 0.38, p < 0.001), followed by online self-efficacy (β = 0.34, p < 0.001) and perceived teacher digital literacy (β = 0.27, p < 0.001). Together, these factors explain 52.3% of the variance in student attitudes, underscoring that content relevance outweighs technological sophistication in driving engagement. These findings refine technology acceptance models and offer actionable insights for combating passive disengagement in college English courses.